Electrostatic spinning preparation method of multifunctional composite nanofiber membrane
Through electrospinning technology, PVDF, PLA and TiO2 are combined to form core-shell fibers and PVDF beaded structures, which solves the problem of insufficient waterproof and breathable performance of windbreakers and protective clothing, and achieves high hydrophobicity, breathability and thermal regulation functions. Multifunctional nanofiber membrane improves the adaptability and environmental protection of the material.
Patent Information
- Application Number
- CN202411349647.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-17
AI Technical Summary
The existing jackets and protective clothing cannot take into account both waterproof and breathable properties, and the lack of temperature regulation functions, resulting in insufficient adaptability in a changing environment.
The electrospinning preparation method of multifunctional composite nanofiber membrane is used to combine PVDF, PLA and TiO2 and other materials, and the core-shell fiber and PVDF beaded structure are formed using coaxial and uniaxial electrospinning technology to achieve high hydrophobicity of the material. , breathability and thermal regulation function.
The prepared materials have excellent hydrophobicity, breathability, UV resistance and thermal regulation performance, and the process flow is simple, non-toxic, and environmentally friendly.
Smart Images

Figure CN119321021A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional fiber production, and in particular to an electrostatic spinning preparation method for a multifunctional composite nanofiber membrane. Background Art
[0002] Traditional fibers prevent skin temperature from being too low by isolating heat. The insulation effect mainly depends on the thickness and density of the fabric. It cannot adjust to wet, cold, and hot environments autonomously, and cannot meet people's higher demands for fabrics. Intelligent temperature-regulating fiber is a new type of functional fiber developed by combining phase change materials with fiber manufacturing technology. It can use the phase change of phase change materials to absorb or release heat to keep the temperature constant, and has broad application prospects.
[0003] Problems such as air pollution and global warming have prompted people to develop smart fabrics that are environmentally friendly, clean, and have heat dissipation (insulation) effects. Phase change materials have attracted people's attention due to their excellent performance. They can release or store heat through phase changes and are good energy-saving materials. However, leakage is inevitable when it changes phase, which greatly limits its practical application. At present, people often use fabric finishing methods, microcapsule treatment methods, hollow fiber impregnation methods, electrospinning methods, etc. to fix phase change materials.
[0004] Jackets are essential equipment for outdoor sports. The reason why they are the first choice of outerwear for all outdoor enthusiasts is due to their all-weather functions. Jackets are required to have good waterproof properties. Whether in humid places or walking in windy and rainy environments, they can effectively block the invasion of rain, frost and snow, so that water cannot penetrate into the clothes and make you feel damp and cold. At the same time, they also require good breathability. When doing outdoor sports with a lot of exercise, the body naturally sweats and the skin exhales a lot of moisture. If it cannot be quickly discharged from the body, it will inevitably cause the sweat to be trapped between the body and the clothes, making people soaked. In rainy weather, it will make people feel even more damp and cold. Especially in severe cold conditions such as mountains and canyons, the body's coldness and hypothermia are very dangerous, so good breathability of clothing is very important.
[0005] Protective clothing is mainly used in firefighting, military industry, shipbuilding, petroleum, chemical industry, painting, cleaning and disinfection, laboratories and other industries and departments. In order to maintain the hygiene of the wearer, protective clothing commonly includes waterproof clothing, oil-proof clothing, etc., which require comfortable wearing, good hand feel, strong tensile strength, breathable and waterproof functions.
[0006] Existing jackets and protective clothing cannot take into account both waterproof and breathable properties, and do not have temperature regulation functions, so their ability to adapt to the environment is not strong. Summary of the invention
[0007] The purpose of the present invention is to provide an electrospinning preparation method for a multifunctional composite nanofiber membrane, which has good UV resistance, waterproofness, breathability, self-cleaning and thermal regulation functions, excellent mechanical properties and degradability, and can be applied to the production of assault jackets, protective clothing, etc.
[0008] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a multifunctional composite nanofiber membrane by electrospinning, comprising the following steps: Step 1: Add PVDF and PLA to the first mixed solvent in sequence, add TiO2 while stirring, and stir at 65-70°C for 7-8 hours to obtain a shell layer solution; melt n-octadecane at 50°C to obtain a core layer solution; Step 2, adding PVDF to the second mixed solvent, stirring at 35-40° C. for 3-4 hours to obtain a PVDF electrospinning solution; Step 3, control the ambient temperature to 45-50 ° C, add the shell solution, core solution and PVDF electrospinning solution into the needles of different syringes, connect the needles of the shell solution and the core solution to the coaxial needle and use coaxial electrospinning to form core-shell fibers, connect the needle of the PVDF electrospinning solution to the uniaxial needle and use uniaxial electrospinning to form PVDF beads, both the coaxial needle and the uniaxial needle are connected to the positive electrode of the high-voltage DC power supply, and the receiving roller wrapped in aluminum foil is connected to the negative electrode of the high-voltage DC power supply. The distance between the receiving roller and the coaxial needle and the uniaxial needle is adjusted, and the injection speed of the shell solution, the core solution and the PVDF electrospinning solution is adjusted. High voltage is provided to form a PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fibers and PVDF beads on the aluminum foil.
[0009] Polylactic acid (PLA) has excellent degradability and mechanical properties. Polyvinylidene fluoride (PVDF) has excellent hydrophobicity, but the mechanical properties of the fiber formed by spinning polyvinylidene fluoride alone are poor. The present invention uses polylactic acid and polyvinylidene fluoride to form a composite fiber, taking into account both hydrophobicity and mechanical properties, while also ensuring degradability. When electrospinning polyvinylidene fluoride and polylactic acid, the choice of solvent has a great influence on the solution. When N,N-dimethylformamide is used alone as a solvent, the needle is easily blocked and spinning is difficult. Therefore, a mixed solvent of N,N-dimethylformamide, N,N-dimethylacetamide and acetone is selected. n-Octadecane is a non-toxic liquid with a low melting point, which has the advantages of high enthalpy value and stable chemical properties. It can be used as a core layer material to realize effective core-shell phase change fibers.
[0010] In the present invention, the shell solution and the core solution are formed into core-shell fibers by coaxial electrospinning, and the PVDF electrospinning solution is formed into a PVDF beaded structure by uniaxial electrospinning. Coaxial electrospinning and uniaxial electrospinning use the same voltage and different spinneret holes, and form a composite material on the same receiving plate (receiving roller wrapped with aluminum foil). The PVDF beaded structure not only greatly improves the hydrophobicity of the material, but also significantly improves the air permeability of the material. Super strong hydrophobicity brings good self-cleaning performance.
[0011] The invention controls the solvent composition and mixing temperature of the electrospinning solution so that the PVDF molecular chain cannot be fully stretched, thereby spinning to form a specific PVDF beaded structure.
[0012] Preferably, in the shell layer solution, the PVDF content is 5-9wt%, the PLA content is 5-9wt%, and the TiO2 content is 1-2wt%.
[0013] Preferably, the first mixed solvent is formed by mixing N,N-dimethylformamide, N,N-dimethylacetamide and acetone in a mass ratio of 0.6-0.8:02-0.3:0.2-0.3.
[0014] Preferably, the second mixed solvent is formed by mixing N,N-dimethylacetamide and acetone in a mass ratio of 0.3-0.4:0.1-0.2.
[0015] Preferably, the PVDF content in the PVDF electrospinning solution is 13 wt %.
[0016] Preferably, the injection rate of the shell solution is 0.6-0.8 mL / h, and the injection rate of the core solution is 0.1-0.2 mL / h.
[0017] Preferably, the positive electrode voltage is 20-22 kV, the negative electrode voltage is -1.5 kV, and the spinning distance is 18-20 cm.
[0018] Preferably, the injection rate of the PVDF electrospinning solution is 0.6-0.8 mL / h.
[0019] The beneficial effects of the present invention are: 1) A multifunctional material with high enthalpy, high hydrophobicity and UV resistance was prepared by combining coaxial electrospinning with uniaxial electrospinning; 2) Coaxial electrospinning technology enables polymers that cannot directly encapsulate phase change materials to encapsulate a large amount of phase change materials, and can prepare fibers with core-shell structures; 3) By introducing the PVDF beaded structure, the hydrophobicity of the material is greatly improved; 4) By adding the UV shielding agent TiO2 into the shell layer, the material's UV resistance is enhanced; 5) The materials prepared by electrospinning not only have improved elongation at break and tensile strength, but also have significantly improved air permeability, hydrophobicity, UV resistance and thermal regulation. 6) The preparation process is simple, non-toxic and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] FIG1 is a process flow chart of the present invention.
[0021] FIG. 2 is a scanning electron microscope photograph of the material of the present invention.
[0022] FIG. 3 is a DSC curve diagram of the material of the present invention.
[0023] FIG. 4 is the UV transmittance curve of the material of the present invention.
[0024] FIG. 5 is a thermogravimetric curve of the material of the present invention.
[0025] FIG. 6 is a stress-strain curve of the material of the present invention.
[0026] FIG. 7 is a microscopic view of the PVDF beaded structure. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described in detail below through specific embodiments.
[0028] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.
[0029] Embodiment 1: Take 0.7 g of polyvinylidene fluoride and 0.7 g of polylactic acid and put them into a mixed solution of 8.45 g of N,N-dimethylformamide, N,N-dimethylacetamide and acetone (mixed in a mass ratio of 0.6:0.2:0.2), add 0.15 g of TiO2 while stirring, and stir at 70 °C for 7 hours to obtain a shell solution.
[0030] Take 5 g of n-octadecane and melt it at 50 °C to obtain a uniform core layer solution.
[0031] 1.3 g of polyvinylidene fluoride was added to 8.7 g of a mixed solvent of N,N-dimethylformamide and acetone (mixed in a mass ratio of 0.3:0.1), and stirred at 40° C. for 3 hours to obtain a polyvinylidene fluoride electrospinning solution.
[0032] The ambient temperature was controlled at 50 °C, and the shell solution, core solution and electrospinning solution were added to the needles of different syringes (10 mL). The needles of the shell solution and the core solution were connected to a coaxial needle for coaxial electrospinning to form core-shell fibers, and the needle of the electrospinning solution was connected to a uniaxial needle for uniaxial electrospinning to form PVDF beads ( Figure 7 ), the coaxial needle and the uniaxial needle were both connected to the positive electrode of a high-voltage DC power supply, the receiving roller wrapped in aluminum foil was connected to the negative electrode of the high-voltage DC power supply, the distance (spinning distance) between the receiving roller and the coaxial needle and the uniaxial needle was adjusted to 18 cm, the injection speed of the shell solution was adjusted to 0.6 mL / h, the injection speed of the core solution was adjusted to 0.15 mL / h, and the injection speed of the electrospinning solution was adjusted to 0.6 mL / h, the positive electrode voltage was 22 kV, and the negative electrode voltage was -1.5 kV. High voltage was provided to form a PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fibers and PVDF beads on the aluminum foil.
[0033] After testing, the phase change latent heat of PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane is 109.18 J / g, the tensile strength is 3.77 MPa, and the elongation at break is 76.14%. The UV protection factor is 200.5, the hydrophobic angle is 147.6°, and the air permeability is 2433.84 g·d -1 ·m -2 .
[0034] Example 2 Take 0.5 g of polyvinylidene fluoride and 0.9 g of polylactic acid and put them into a mixed solution of 8.5 g of N,N-dimethylformamide, N,N-dimethylacetamide and acetone (mixed in a mass ratio of 0.7:0.2:0.2), add 0.1 g of TiO2 while stirring, and stir at 67°C for 7.5 hours to obtain a shell solution.
[0035] Take 5 g of n-octadecane and melt it at 50 °C to obtain a uniform core layer solution.
[0036] 1.5 g of polyvinylidene fluoride was added to 10 g of a mixed solvent of N,N-dimethylformamide and acetone (mixed in a mass ratio of 0.3:0.2), and stirred at 37° C. for 3.5 hours to obtain an electrospinning solution of polyvinylidene fluoride.
[0037] The ambient temperature was controlled at 47 °C, and the shell solution, core solution and electrospinning solution were added to the needles of different syringes (10 mL). The needles of the shell solution and the core solution were connected to a coaxial needle for coaxial electrospinning to form core-shell fibers. The needle of the electrospinning solution was connected to a uniaxial needle for uniaxial electrospinning to form PVDF beads. Both the coaxial needle and the uniaxial needle were connected to the positive electrode of a high-voltage DC power supply, and a receiving roller wrapped in aluminum foil was connected to the negative electrode of the high-voltage DC power supply. The distance (spinning distance) from the receiving roller to the coaxial needle and the uniaxial needle was adjusted to 19 cm. The injection speeds of the shell solution, the core solution and the electrospinning solution were adjusted to 0.7 mL / h, 0.1 mL / h and 0.7 mL / h, the positive voltage was 21 kV, and the negative voltage was -1.5 kV, providing high voltage to form PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fiber and PVDF beads on aluminum foil.
[0038] After testing, the phase change latent heat of PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane is 103.13 J / g, the tensile strength is 2.35 MPa, and the elongation at break is 59.44%. The UV protection factor is 127.4, the hydrophobic angle is 141.7°, and the air permeability is 2373.62 g·d -1 ·m -2 .
[0039] Example 3 Take 0.9 g of polyvinylidene fluoride and 0.5 g of polylactic acid and put them into a mixed solution of 8.4 g of N,N-dimethylformamide, N,N-dimethylacetamide and acetone (mixed in a mass ratio of 0.8:0.3:0.3), add 0.2 g of TiO2 while stirring, and stir at 65 °C for 8 hours to obtain a shell solution.
[0040] Take 5 g of n-octadecane and melt it at 50 °C to obtain a uniform core layer solution.
[0041] 1.3 g of polyvinylidene fluoride was added to 8.7 g of a mixed solvent of N,N-dimethylformamide and acetone (mixed in a mass ratio of 0.4:0.1), and stirred at 35° C. for 4 hours to obtain an electrospinning solution of polyvinylidene fluoride.
[0042] The ambient temperature was controlled at 45 °C, and the shell solution, core solution and electrospinning solution were added to the needles of different syringes (10 mL). The needles of the shell solution and the core solution were connected to a coaxial needle for coaxial electrospinning to form core-shell fibers. The needle of the electrospinning solution was connected to a uniaxial needle for uniaxial electrospinning to form PVDF beads. Both the coaxial needle and the uniaxial needle were connected to the positive electrode of a high-voltage DC power supply, and a receiving roller wrapped in aluminum foil was connected to the negative electrode of the high-voltage DC power supply. The distance (spinning distance) between the receiving roller and the coaxial needle and the uniaxial needle was adjusted to 20 cm. The injection speeds of the shell solution, the core solution and the electrospinning solution were adjusted to 0.8 mL / h, 0.2 mL / h and 0.8 mL / h, the positive voltage was 20 kV, and the negative voltage was -1.5 kV, providing high voltage to form PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fiber and PVDF beads on aluminum foil.
[0043] After testing, the phase change latent heat of PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane is 100.62 J / g, the tensile strength is 4.4 MPa, and the elongation at break is 55.62%. The UV protection factor is 193.6, the hydrophobic angle is 139.5°, and the air permeability is 2257.8 g·d -1 ·m -2 .
[0044] Comparative Example 1: Take 0.7 g of polyvinylidene fluoride and 0.7 g of polylactic acid and put them into a mixed solution of 8.45 g of N,N-dimethylformamide, N,N-dimethylacetamide and acetone (mixed in a mass ratio of 0.6:0.2:0.2), add 0.15 g of TiO2 while stirring, and stir at 70 °C for 7 hours to obtain a shell solution.
[0045] Take 5 g of n-octadecane and melt it at 50 °C to obtain a uniform core layer solution.
[0046] The ambient temperature was controlled at 50 ℃, and the shell solution and the core solution were added into the needles of different syringes (10 mL). The needles of the shell solution and the core solution were connected to a coaxial needle, which was connected to the positive electrode of a high-voltage DC power supply. The receiving roller wrapped with aluminum foil was connected to the negative electrode of the high-voltage DC power supply. The distance between the receiving roller and the coaxial needle (spinning distance) was adjusted to 18 cm. The injection speeds of the shell solution and the core solution were adjusted to 0.6 mL / h and 0.15 mL / h, respectively. The positive electrode voltage was 22 kV, and the negative electrode voltage was -1.5 kV. High voltage was provided to form a PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fibers and PVDF beads on the aluminum foil.
[0047] The test showed that the hydrophobic angle of PVDF / PLA / TiO2@Oct composite nanofiber membrane was 135.5°. The air permeability was 1983.42 g·d -1 ·m -2 .
[0048] Comparative Example 2: 1.4 g of polylactic acid was put into a mixed solution of 8.45 g of N,N-dimethylformamide, N,N-dimethylacetamide and acetone (mixed in a mass ratio of 0.6:0.2:0.2), 0.15 g of TiO2 was added while stirring, and the mixture was stirred at 70 °C for 7 hours to obtain a shell solution.
[0049] Take 5 g of n-octadecane and melt it at 50 °C to obtain a uniform core layer solution.
[0050] The ambient temperature was controlled at 50 °C, and the shell solution and the core solution were added to the syringes of different syringes (10 mL). The syringes of the shell solution and the core solution were connected to a coaxial needle, which was connected to the positive electrode of a high-voltage DC power supply. The receiving roller wrapped with aluminum foil was connected to the negative electrode of the high-voltage DC power supply. The distance between the receiving roller and the coaxial needle (spinning distance) was adjusted to 18 cm. The injection speeds of the shell solution and the core solution were adjusted to 0.6 mL / h and 0.15 mL / h, respectively. The positive electrode voltage was 22 kV, and the negative electrode voltage was -1.5 kV. High voltage was provided to form a core-shell fiber PLA / TiO2@Oct nanofiber membrane on the aluminum foil.
[0051] After testing, the hydrophobic angle of the PLA / TiO2@Oct composite nanofiber membrane was 123°.
[0052] The process of the present invention is as follows Figure 1 As shown in FIG. 1 , the coaxial electrospinning device is composed of two needle tubes, and the PVDF electrospinning solution is separately involved in electrospinning. Figure 2 As shown in the figure, it can be seen that a large number of pearl-like structures are interspersed in the visible fibers, and there are also a small number of spindles. The presence of the pearl-like structure expands the spacing between the P&PPT@Oct fibers and increases the pores between the fibers. The pearl-like structures are also connected in series through the PVDF fibers to form a bead-fiber structure. The DSC curve of the sample in Example 1 is shown in Figure 3 As shown, from Figure 3 It can be seen that the latent heat of phase change of the fiber membrane is 109.18 J / g. The UV transmission curve of the sample of Example 1 is as follows Figure 4 As shown in Figure 1, with the increase of TiO2 mass fraction, the UV transmittance of the nanofiber membrane is significantly reduced. Figure 5As shown in the figure, it can be seen that the thermal decomposition of P&PPT@Oct is divided into three stages. The three stages of thermal decomposition occur at 250 ℃, 370 ℃ and 460 ℃, corresponding to the thermal decomposition of n-octadecane, polylactic acid and polyvinylidene fluoride, respectively.
[0053] Figure 6 It shows that the higher the PVDF content, the greater the tensile strength of the membrane, but the relative elongation at break becomes worse. The defect of elongation at break is compensated by blending with PLA. Compared with pure PVDF membrane and PLA membrane, the composite nanofiber membrane prepared in Example 1 of the present invention has the highest elongation at break, reaching 76.14%. At the same time, the tensile strength is 3.77 MPa. Figure 7 It shows that under the conditions of the present invention, the nanofibers prepared by uniaxial electrospinning of polyvinylidene fluoride electrospinning liquid are not uniformly distributed nanofibers, but a microsphere-fiber interpenetrating structure, forming an obvious beaded structure.
[0054] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A method for preparing a multifunctional composite nanofiber membrane by electrospinning, characterized in that: The steps include: Step 1: Add PVDF and PLA to the first mixed solvent in sequence, add TiO2 while stirring, and stir at 65-70°C for 7-8 hours to obtain a shell layer solution; melt n-octadecane at 50°C to obtain a core layer solution; Step 2, adding PVDF to the second mixed solvent, stirring at 35-40° C. for 3-4 hours to obtain a PVDF electrospinning solution; Step 3, control the ambient temperature to 45-50 ° C, add the shell solution, core solution and PVDF electrospinning solution into the needles of different syringes, connect the needles of the shell solution and the core solution to the coaxial needle and use coaxial electrospinning to form core-shell fibers, connect the needle of the PVDF electrospinning solution to the uniaxial needle and use uniaxial electrospinning to form PVDF beads, both the coaxial needle and the uniaxial needle are connected to the positive electrode of the high-voltage DC power supply, and the receiving roller wrapped in aluminum foil is connected to the negative electrode of the high-voltage DC power supply. The distance between the receiving roller and the coaxial needle and the uniaxial needle is adjusted, and the injection speed of the shell solution, the core solution and the PVDF electrospinning solution is adjusted. High voltage is provided to form a PVDF&PVDF / PLA / TiO2@Oct composite nanofiber membrane composed of core-shell fibers and PVDF beads on the aluminum foil.
2. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: In the shell layer solution, the PVDF content is 5-9wt%, the PLA content is 5-9wt%, and the TiO2 content is 1-2wt%.
3. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The first mixed solvent is prepared by mixing N,N-dimethylformamide, N,N-dimethylacetamide and acetone in a mass ratio of 0.6-0.8:02-0.3:0.2-0.
3.
4. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The second mixed solvent is prepared by mixing N,N-dimethylacetamide and acetone in a mass ratio of 0.3-0.4:0.1-0.
2.
5. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The PVDF content in the PVDF electrospinning solution is 13wt%.
6. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The injection rate of the shell solution was 0.6-0.8 mL / h, and the injection rate of the core solution was 0.1-0.2 mL / h.
7. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The injection rate of PVDF electrospinning solution was 0.6-0.8 mL / h.
8. The electrospinning preparation method of a multifunctional composite nanofiber membrane according to claim 1, characterized in that: The positive electrode voltage was 20-22 kV, the negative electrode voltage was -1.5 kV, and the spinning distance was 18-20 cm.
Citation Information
Patent Citations
High-efficiency and low-resistance nanofiber air filtering material for gauze mask and preparation method of filtering material
CN104645715A
Flexible TiO2 / PVDF@MoS2 composite nanofiber with visible light catalytic performance and preparation method thereof
CN108325564A
Core-shell self-repairing fiber bead type electrospinning material based on pH response and synthesis method and application thereof
CN110318120A
Preparation method of waterproof, moisture-permeable and temperature-adjustable intelligent nanofiber membrane
CN112160072A
Polylactic acid micro-nano multistage fiber filtering membrane with beaded structure as well as preparation method and application of polylactic acid micro-nano multistage fiber filtering membrane
CN117282285A
Cited By
Hot airflow protective article based on multi-component micro-nano fiber membrane
CN119928389A
Preparation method of composite phase-change temperature-regulating organic fiber membrane material with flexible core-shell structure
CN120138888A
Method for preparing nanofiber wrap yarn for personal thermal management through coaxial conjugate electrostatic spinning
CN120174524A